Peranan Aplikasi Artificial Intelligence untuk Mendukung Proses Pembelajaran di SMKS YPSEI Kota Palangka Raya - Yunida Iashania; Onie Dian Sanitha; Asri Fridtriyanda; Novera Kristianti (I-Com: Indonesian Community Journal, 2024)
The world of education can adapt to the changes that occur in the current digital era so that it remains relevant to the changes and developments of the times. The use of artificial intelligence in the field of education is increasingly being used, especially in learning activities. This training includes an introductory session on Canva and practice using Canva applications. Through an approach by introducing the Canva application for teachers (teachers) to design creative learning tasks, such as infographics, presentations and educational videos, which can increase student innovation. The results of this training showed significant improvements in the technology skills of students and teachers and the quality of the learning materials produced. Training using the Canva application specifically for teachers at SMKS YPSEI Palangka Raya City reaped positive results, with participants giving a very satisfied assessment of the activity. Keywords: Canva, Teacher, Artificial Intelligence, Training